#1**+1 **

The one before the last choice (Third one, C)

First simplify the equation of the circle to the general formula which is (x-h)^2+(y-k)^2=r^2

so

(x^2+x)+(y^2-6y)-2

Notice both of these we need to complete the square

so

(x^2+x+1/4)+(y^2-6y+9)=+2+9+1/4 (Why did we add 9 and 1/4? Because anything we add to one side of an equation must be added to the other side as well as multiply and divide and subtraction)

so this basically simplifies to

(x+1/2)^2+(y-3)^2=11.25 (Notice we are in the general equation form of the circle's equation which is again, (x-h)^2+(y-k)^2=r^2

Find the center would be finding x and y

so x and y must make the barract=0 in order to be center

x+1/2=0

x=-1/2

y-3=0

y=3

Radius^2 is 11.25 (Notice it is squared already due to general form)

So radius is = sqrt(11.25) equal to 3sqrt(5)/2

Guest Oct 24, 2019

#1**+1 **

Best Answer

The one before the last choice (Third one, C)

First simplify the equation of the circle to the general formula which is (x-h)^2+(y-k)^2=r^2

so

(x^2+x)+(y^2-6y)-2

Notice both of these we need to complete the square

so

(x^2+x+1/4)+(y^2-6y+9)=+2+9+1/4 (Why did we add 9 and 1/4? Because anything we add to one side of an equation must be added to the other side as well as multiply and divide and subtraction)

so this basically simplifies to

(x+1/2)^2+(y-3)^2=11.25 (Notice we are in the general equation form of the circle's equation which is again, (x-h)^2+(y-k)^2=r^2

Find the center would be finding x and y

so x and y must make the barract=0 in order to be center

x+1/2=0

x=-1/2

y-3=0

y=3

Radius^2 is 11.25 (Notice it is squared already due to general form)

So radius is = sqrt(11.25) equal to 3sqrt(5)/2

Guest Oct 24, 2019